Impact of Epstein-Barr Virus on Peripheral T-Cell Lymphoma Not Otherwise Specified and Angioimmunoblastic T-Cell Lymphoma - Kim, Tong-Yoon; Min, Gi-June; Jeon, Young-Woo; Park, Sung-Soo; Park, Silvia; Shin, Seung-Hawn; Yahng, Seung-Ah; Yoon, Jae-Ho; Lee, Sung-Eun; Cho, Byung-Sik; Eom, Ki-Seong; Kim, Yoo-Jin; et al. (Frontiers in Oncology, 2022)
Purpose: The significance of Epstein-Barr virus (EBV) infections for the prognosis of patients with peripheral T-cell lymphomas (PTCLs), specifically angioimmunoblastic T-cell lymphoma (AITL) and PTCL not otherwise specified (PTCL-NOS), remains unclear. The Epstein-Barr encoding region can be used to detect EBV in tissue sections by in situ hybridization (ISH) and by polymerase chain reaction (PCR) assays of peripheral blood samples from patients with PTCLs. This study compared the outcomes patients with AITL or PTCL-NOS for whom the presence of EBV infection was assessed by these two methods. Patients and Methods: This was a retrospective study of patients newly diagnosed with AITL or PTCL-NOS. All patients were selected from a single transplantation center. EBV-positive lymphomas were detected at the time of diagnosis in tissue sections by ISH or in the blood by PCR. Results: Among the 140 patients with histologically confirmed AITL or PTCL, 105 were EBV-positive. The 3-year overall survival of patients with EBV-positive TCL was 43.3% compared to 68.6% in patients with EBV-negative TCL (p = .01). Patients treated with autologous or allogeneic hematopoietic stem cell transplantation (n = 26 and n = 11, respectively) or chemotherapy (n = 66) had 3-year survival rates of 68.4%, 62.3%, and 30.1%, respectively (p < .02). Patients with EBV-positive TCL had a better prognosis after treatment with hematopoietic stem cell transplantation compared to chemotherapy alone, but no difference was seen among patients with EBV-negative TCL. Conclusions: EBV infection was shown to negatively affect the clinical outcomes of patients with TCL. Stem cell transplantation has been found to be an effective treatment for EBV-associated lymphomas. Further investigations are warranted to determine the optimal treatment for these patients.